Impact of tides in a baroclinic circulation model of the Adriatic Sea. Issue 1 (27th January 2013) - Guarnieri, A.; Pinardi, N.; Oddo, P.; Bortoluzzi, G.; Ravaioli, M.
Abstract: [1] The impact of tides in the circulation of the Adriatic Sea is investigated by means of a nested baroclinic numerical ocean model. Tides are introduced using a modified Flather boundary condition at the open edge of the domain. The results show that tidal amplitudes and phases are reproduced correctly by the baroclinic model and tidal harmonic constants errors are comparable with those resulting from the most consolidated barotropic models. Numerical experiments were conducted to estimate and assess the impact of (i) the modified Flather lateral boundary condition; (ii) tides on temperature, salinity, and stratification structures in the basin; and (iii) tides on mixing and circulation in general. Tides induce a different momentum advective component in the basin, which in turn produces a different distribution of water masses in the basin. Tides impact on mixing and stratification in the River Po region (northwestern Adriatic) and induce semidiurnal fluctuations of salinity and temperature, in all four seasons for the former and summer alone for the latter. A clear presence of internal tides was evidenced in the northern Adriatic Sea basin, corroborating previous findings. Key Points: Tides can be well reproduced in the Adriatic Sea through baroclinic model Tides induce a different momentum advective component in the Adriatic Sea basin Tides impact on mixing and stratification; evidence of internal tides